2016
DOI: 10.1128/jvi.00463-16
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cytomegalovirus Dense Bodies by Scalable Bioprocess Methods Maintains Immunogenicity and Improves Neutralizing Antibody Titers

Abstract: With the goal of developing a virus-like particle-based vaccine based on dense bodies (DB) produced by human cytomegalovirus (HCMV) infections, we evaluated scalable culture, isolation, and inactivation methods and applied technically advanced assays to determine the relative purity, composition, and immunogenicity of DB particles. Our results increase our understanding of the benefits and disadvantages of methods to recover immunogenic DB and inactivate contaminating viral particles. IMPORTANCEDevelopment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The antibody response resulting from vaccination with these DBs was also shown to prevent infection of both fibroblasts and epithelial cells by the clinical CMV isolate VR1814 in cell culture (112). Methods to scale up the processes of manufacture and purification have been previously described (115). The Serum Institute of India has licensed the technology for production of a DB vaccine, designated CAP CMV001, from Vakzine Projekt Management GmbH.…”
Section: Vaccines In Preclinical Developmentmentioning
confidence: 99%
“…The antibody response resulting from vaccination with these DBs was also shown to prevent infection of both fibroblasts and epithelial cells by the clinical CMV isolate VR1814 in cell culture (112). Methods to scale up the processes of manufacture and purification have been previously described (115). The Serum Institute of India has licensed the technology for production of a DB vaccine, designated CAP CMV001, from Vakzine Projekt Management GmbH.…”
Section: Vaccines In Preclinical Developmentmentioning
confidence: 99%
“…We and others have shown that DBs are highly immunogenic, bearing the exceptional capacity to induce both humoral and cellular immune responses without requiring an adjuvant (25,28,29,31,33,34). DBs induce maturation and activation of immature dendritic cells in addition, likely explaining their impact on the priming of immune responses (30).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely related to the maturation and activation of dendritic cells (DCs) following incubation of these cells with DBs (30). DB application also induces high levels of NT-abs against HCMV infection (25,28,29,31). Since viral envelope proteins are inserted in their functional conformation into the envelopes of DBs, these particles likely induce humoral responses comparable to those induced by viral infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, an impact of pUL25 loss either on the morphogenesis of DBs within the cell or on the yield of DBs that could be purified from infected cell culture supernatants was not seen (not shown). DBs are a promising vaccine candidate (31)(32)(33)(34)(35). Production of DBs depends on their purification from infected cell cultures.…”
Section: Discussionmentioning
confidence: 99%